Improving Students’ Learning Outcomes in Natural Science Subject for Third Grade of Elementary School Through Video Media - Muktar Bahruddin Panjaitan; Mashudi Alamsyah; Martua Ferry Siburian; Endang Fatmawati; Uslan Uslan; Gunaria Siagian (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This research study explored the use of video media to improve science learning outcomes for third-grade elementary school students in Indonesia. To conduct the survey, the researchers select a representative sample of third-grade students from a target population, ensuring that the sample adequately represents the diversity of students in terms of backgrounds, academic abilities, and prior exposure to video media in science education. A qualitative survey methodology was employed, and data were collected from a sample of 27 students. The findings indicate that video media positively impacted students' perception of science learning. Students demonstrated high levels of interest and engagement, found the content clear and understandable, experienced improved retention of knowledge, enjoyed self-paced learning, engaged in collaborative experiences, and benefited from the multimodal nature of video media. These findings highlight the potential of video media as a valuable tool in enhancing science education for elementary school students